2020
DOI: 10.1186/s13018-020-01706-6
|View full text |Cite
|
Sign up to set email alerts
|

Facet joint parameters which may act as risk factors for chronic low back pain

Abstract: Background: Facet orientation (FO) and facet tropism (FT) are two important structural parameters of lumbar facet joint. The purpose of this study was to evaluate the association between facet joint parameters and chronic low back pain (LBP). Methods: From June 2017 to January 2019, a total of 542 cases were enrolled in this study. There were 237 males and 305 females with a mean age of 35.8 years (range 18~59 years). All the cases were divided into a LBP group (LBP group) and a non-LBP group (N-LBP group) in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…However, in other studies, facet asymmetry was significantly related to lumbar stenosis, 14 spondylolisthesis, 26 and low back pain. 25 In this study, FJ tropism was not strongly correlated with FJ OA but was a risk factor for LFS. This seems to be a combination of the abovementioned views.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…However, in other studies, facet asymmetry was significantly related to lumbar stenosis, 14 spondylolisthesis, 26 and low back pain. 25 In this study, FJ tropism was not strongly correlated with FJ OA but was a risk factor for LFS. This seems to be a combination of the abovementioned views.…”
Section: Discussioncontrasting
confidence: 49%
“…23 Studies on young populations have demonstrated that coronal orientation of the FJ is a risk factor for disc herniation and low back pain. 24,25 This evidence indicated that as lumbar degeneration progressed, the FJs were remodeled to a sagittal orientation to reduce loading. However, further studies are required to identify these pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“… 47 - 49 After CDA surgery, the kinematic and biomechanical changes could have adverse effects on the facet joints, 32 , 50 , 51 and the non-physical stress on the facet joints could result in facetogenic neck pain, especially in asymmetric 3-joint complex. 22 , 52 Differences in pain may account for the decreased C2-C7 ROM in the asymmetric group. Whereas, clinical scores showed no difference between symmetric and asymmetric groups in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Linov et al 36 confirmed a significant association between sagittal orientation and OA of the LFJ at level L4-L5 in a cross-sectional study. Yang et al 37 demonstrated that FJT may play an important role in the pathogenesis of lumbar degenerative diseases, using finite element analysis and contour maps visualization. Ke et al 38 found that the combination of FJO and FJT played an important role in the development of lumbar degeneration, including disc and LFJ.…”
Section: Pathogenesismentioning
confidence: 99%